2022
DOI: 10.1021/acsapm.2c00855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemistry of Silicon Surfaces on the Curing Process and Adhesive Strength for Epoxy Resin

Abstract: The adhesive strength of epoxy resins is generally dependent on the surface chemistry of an adherend. Although the free space, or the nanoscopic void space, formed at the adhered interface due to the curing shrinkage is expected to have a significant impact on the adhesive strength, the molecular picture is not yet well understood. In this study, all-atom molecular dynamics simulations were used to investigate how the curing reaction and thereby adhesive strength of an epoxy resin differed on hydrophilic and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…Below the yield point, the three substrate models exhibited similar stress–strain behaviors, as indicated by the yellow guidance curves in Figure a–i, which show the same curve in each graph. The minor differences between the OH- and H-terminated models are consistent with the results reported recently by Yamamoto et al , in which the interfaces between epoxy resins and OH- and H-terminated Si substrates were compared via MD simulations. Therefore, it can be concluded that the behavior up to the yield point under mode I deformation depends on the diffusional molecular movements (i.e., friction between molecules along with network stretching and partial disentanglement).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Below the yield point, the three substrate models exhibited similar stress–strain behaviors, as indicated by the yellow guidance curves in Figure a–i, which show the same curve in each graph. The minor differences between the OH- and H-terminated models are consistent with the results reported recently by Yamamoto et al , in which the interfaces between epoxy resins and OH- and H-terminated Si substrates were compared via MD simulations. Therefore, it can be concluded that the behavior up to the yield point under mode I deformation depends on the diffusional molecular movements (i.e., friction between molecules along with network stretching and partial disentanglement).…”
Section: Resultssupporting
confidence: 90%
“…They confirmed that hydroxyl, formyl, carboxyl, and amine groups required different forces and displacements for interfacial fracture. Recently, Yamamoto et al 39 investigated epoxy resins on Si(100) substrates that were fully decorated with SiOH or SiH surface functional groups and showed that the detachment behavior of adhered epoxy resins was characterized by the difference between the surface charges and not by the difference between group type (SiOH or SiH). Additionally, they revealed that this charge (polarization) difference affected both the substrate− polymer gap and polymer motion and reaction.…”
Section: Simulations Of Adhesion Between Sio 2 Substrates and Polymer...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study on the free space at the substrate/epoxy resin interface, the molecular dynamics simulation showed that the free space of 5−10% would be formed by the shrank of the epoxy resin. 52 Evidently, the excess water is not just comprised of water molecules directly bonded to the substrate. [24][25][26][27]53 In the subsequent experiments, the new findings show that some of the excess water molecules are located within the epoxy resin near the interface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since around 2000, AAMD and CGMD simulations have been applied to model the cross-linking structure of epoxy resins. A number of methods have been proposed to improve computational efficiency and obtain sufficiently relaxed structures, and many applications to cross-linking systems have been reported. Following a method proposed by Okabe et al that takes into account the heat generated by the reaction, the curing reaction for a pair of epoxy and amino groups was herein conducted. CGMD simulations were performed while judging the cross-linking reaction at certain time intervals. The reaction was allowed if the beads representing epoxy and amino groups approached within a reaction distance of 0.6 nm and the Arrhenius-type reaction probability k , consisting of the activation energy E a , the gas constant R , local temperature T , and frequency factor A , was greater than a generated random number P [0,1]. k = A .25em exp ( E a R T ) …”
Section: Simulationmentioning
confidence: 99%